The International Collaboration of Pharmacy Journal Editors (ICPJE)formally constituted to foster quality around clinical and social pharmacy practice research publications - Alves da Costa, F. (2024)
The Granada statements were a result of the need to strengthen clinical, social and administrative pharmacy practiceas an area of knowledge that translates into practice, research and policy.As a response, a group of clinical and social pharmacy practice journal editors launched an initiative in Granada in 2022 to discuss ways to improve the quality of publications in this area, which culminated in the Granada statements. Eighteen statementswere developed, clustered into six main domains:1) the appropriate use of terminology; 2) developing impactful abstracts; 3) having the required peer reviews; 4) preventing journal scattering; 5) more effective and wiser use of journal and article performance metrics; and 6)authors' selection of the most appropriate pharmacy practice journal to submit their work. The full Granada statements have been published in 14 journals.1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 These pioneering statements are rooted in similar endeavors undertaken by scholars in other health professions groups, fostering the concept of interdisciplinary consensus and advancing scientific paradigm.15,16 Various chief editors, associated editors, and publishers met again in June 2024, this time in Basel, Switzerland. Following a consensus approach to select a name that best reflected the group scope, mission and vision, the name of the International Collaboration of Pharmacy Journal Editors (ICPJE) was selected. The ICPJE was then born.